Analysis of Escherichia Coli Existance Factors in Street Food at Primary School in Nggrogot Distrct - Nisa, Ihda Farihatun; Woro Kasmini Handayani, Oktia; Raffy Rustiana, Eunike (Public Health Perspective Journal, 2019)
Food availability and security are basic human rights. Lack of attention to food security such as unhygienic food processing can cause health problems. National Food and Drug Agency stated that 27.92% of school children snacks contain hazardous substances ranging from physical, chemical and microbiological. The survey results of 36 primary schools in the Ngronggot District do not have the criteria for a healthy canteen, it causes the access of street frood are increase freely in the Primary School environment. Most of them didn’t have a food production legacy from Health Office or National Food and Drug Agency. The purpose of this study was to determine the most dominant factors among other factors, namely environmental sanitation, sanitation equipment, food handler personal hygiene, the condition of food raw materials, the condition of food storage, and the condition of serving food to the presence of E. coli. This research was quantitative method, with cross sectional approach. The research sample was 48 samples with simple random sampling technique. The instrument used was observation sheets and laboratory test results. Data collection techniques used interviews, observations and laboratory tests. Statistical analysis used Multiple Logistic it is found that the most dominant variable among the other variables is food handler personal hygiene = 0.003. The presence of E. coli indicates microbial contamination in food which results in food borne illness. It is recommended to increase supervision in food processing to reduce bacterial contamination.